Designing and Implementing an Effective Moodle Learning Management System (LMS) to Meet the Needs of Language Teaching and Learning - Prasetya, Rizky Eka; Fenti Sofiani (Edu-Ling: Journal of English Education and Linguistics, 2024)
The objectives of this research was to investigate the challenges encountered in designing and implementing a Moodle LMS for language teaching and learning and explore potential solutions to overcome them. This research was a mixed-methods approach. The sample of this research involved 225 participants: language teachers, learners, and IT support staff. The data were gathered by using two main methods: surveys and focus group discussions, and were analysed by process combined descriptive statistics, t-tests or ANOVA, correlation analysis, and thematic analysis. The findings showed that language teachers require a user-friendly, flexible, and customizable Moodle LMS with access to various multimedia materials and interactive activities. Learner’s value a Moodle LMS that was easy to navigate, with clear instructions and user-friendly interfaces. Technical support and training were also necessary for language teachers to effectively utilize Moodle LMS. The study concluded in conclusion, designing and implementing an effective Moodle LMS meets the specific needs of language teaching and learning required careful consideration of various factors, including the needs of language teachers and learners and technical and pedagogical aspects.